(untitled) (Jurnal Ekonomi dan Bisnis, 2025)
The background to this research is that theoretically, when the value of exports increases, economic growth also increases; However, in the last 30 years, the opposite has happened. That shouldn’t be the case. By using information on economic development, export value and foreign investment value in Indonesia over the last 30 years, researchers want to validate this idea. In this quantitative research, verification tests and reliability tests are used—classical assumption tests which include, for example, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests—as well as hypothesis tests which include F tests, t tests, and Rim Square. Exercise Tested using the t test, the research findings show that the export variable (X1) has a marginally significant influence on Indonesia’s economic development, with a significance value of 0.00 compared to. The decision standard where the sig value <0.05 simultaneously influences two variables, namely exports and foreign investment (PMA), this is shown from the results of the F test giving a Sig value of 0.00, tested using the t test where the variable (X2) is significant or foreign investment of 0.00. The R-square test shows the influence of these two factors is 76.2%.